EFFECT OF DIOIC ACIDS ON FERRIC IRON REDUCTION BY SHEWANELLA ONEIDENSIS MR-1 AND CARBON STEEL CORROSION - KOKBUDAK, HATICE NURSAH (My University, 2017)
Corrosion represents a tremendous burden on infrastructure and industries such as the oil and gas industry. According to National Association of Corrosion Engineers (NACE), total annual cost of steel corrosion in the oil and gas production industry is estimated to be $1.372 billion and over 20% of the corrosion cost is through microbially induced corrosion (Jahaverdashti, 2008). Production water tanks, oil wells and pipes are critical components in the oil and gas industry and are among objects that are most susceptible to corrosion. Maintaining or replacing these can place significant financial strain on the industry. Hence, it is important to determine the cause(s) and the underlying mechanism(s) behind the biological corrosion that occurs in field. Aqueous samples taken from water oil wells and pipes from Putumayo Basin located in Colombia show an abundance of bacterial species such as Shewanella spp, a facultative anaerobic iron-reducing bacteria (IRB). In addition, a number of dicarboxylic (dioic) acids were detected in these tanks that are proposed to arise from the aerobic degradation of hydrocarbons that are present in the environment. In this work, we propose a new microbially influenced corrosion (MIC) mechanism by which dioic acids solubilize ferric iron from a steel surface and the soluble ferric iron is respired by iron reducing bacteria that are present, allowing unbinding of the dioic acid for further ferric iron solubilization, thus increasing the rate of carbon steel corrosion. We studied the effects of three dioic acids that have been found in the production water environment (oxalic acid, malonic acid and succinic acid) as well as two reference ligands (citric acid and nitrilotriacetic acid (NTA)) on this proposed IRB MIC mechanism. Our results show that in the presence of bacteria, the dioic acids increase the concentration of dissolved ferric iron more than in an abiotic environment (oxalate shows nearly a 3-fold increase in dissolved ferric iron concentration). We also observe a decrease on Ecorrosion with oxalate suggesting that the removal efficiency of ferric oxyhydroxide layer from steel surface increased and S. oneidensis MR-1 respiration facilitated. We conclude that our mechanism is valid as a basic mechanism of IRB MIC, but the system is likely more complex due to the adsorption of ligands on the surface and the formation of biofilms.
Keywords: MICROBIAL INDUCED CORROSION